Conjoined twins: twenty years' experience at a reference center in Brazil (Clinics, 2013)
OBJECTIVE: This study reports on the experience of one hospital regarding the surgical aspects, anatomic investigation and outcomes of the management of 21 conjoined twin pairs over the past 20 years. METHODS: All cases of conjoined twins who were treated during this period were reviewed. A careful imaging evaluation was performed to detail the abdominal anatomy (particularly the liver), inferior vena cava, spleen and pancreas, either to identify the number of organs or to evaluate the degree of organ sharing. RESULTS: There were eight sets of ischiopagus twins, seven sets of thoracopagus twins, three sets of omphalopagus twins, two sets of thoraco-omphalo-ischiopagus twins and one set of craniopagus twins. Nine pairs of conjoined twins could not be separated due to the complexity of the organs (mainly the liver and heart) that were shared by both twins; these pairs included one set of ischiopagus twins, six sets of thoracopagus twins and one set of thoraco-omphalo-ischiopagus twins. Twelve sets were separated, including seven sets of ischiopagus twins, three sets of omphalopagus twins, one set of thoracopagus twins and one set of craniopagus conjoined twins. The abdominal wall was closed in the majority of patients with the use of mesh instead of the earlier method of using tissue expanders. The surgical survival rate was 66.7%, and one pair of twins who did not undergo separation is currently alive. CONCLUSION: A detailed anatomic study of the twins and surgical planning must precede separation. A well-prepared pediatric surgery team is sufficient to surgically manage conjoined twins.